Mechanism and Kinetics of Punch Sticking of Pharmaceuticals - Paul, Shubhajit; Taylor, Lisa J.; Murphy, Brendan; Krzyzaniak, Joseph; Dawson, Neil; Mullarney, Matthew P.; Meenan, Paul; Sun, Changquan Calvin (Journal of pharmaceutical sciences, 2017)
Adherence of powder onto tablet tooling, known as punch sticking, is one of the tablet manufacturing problems that need to be resolved. An important step toward the resolution of this problem is to quantify sticking propensity of different active pharmaceutical ingredients (APIs) and understand physicochemical factors that influence sticking propensity. In this study, mass of adhered material onto a removable upper punch tip as a function of number of compression is used to monitor sticking kinetics of 24 chemically diverse compounds. We have identified a mathematical model suitable for describing punch sticking kinetics of a wide range of compounds. Chemical analyses have revealed significant enrichment of API content in the adhered mass. Based on this large set of data, we have successfully developed a new punch sticking model based on a consideration of the interplay of interaction strength among API, excipient, and punch surface. The model correctly describes the general shape of sticking profile, that is, initial rise in accumulated mass followed by gradual increase to a plateau. It also explains why sometimes sticking is arrested after monolayer coverage of punch surface by API (punch filming), while in other cases, API buildup is observed beyond monolayer coverage.